Ishiuchi Miyako - postwar shadows - Ishiuchi, Miyako 1947-; Maddox, Amanda 1948- (The J. Paul Getty Museum, 2015)
A maverick in the history of photography, lshiuchi Miyako burst onto the photography scene in Tokyo in the mid-1970s, at a time when men dominated the field in Japan. Working prodigiously over the last forty years, she has created an impressive oeuvre and quietly influenced generations of photographers born in the postwar era. Recipient of the prestigious Hasselblad Award in 2014, lshiuchi ranks as one of the most significant photographers working in Japan today. Spurred by her contentious relationship with her hometown, Yokosuka - site of an important American naval base since 1945 - lshiuchi chose that city as her first serious photographic subject. Grainy, moody, and deeply personal, these early projects established her career. This choice of subject also defined the beginning of lshiuchi's extended exploration of American occupation and the shadows it cast over postwar Japan. lshiuchi has since addressed the theme of occupation both indirectly - through her photographs of scars, skin, and other markers of time on the human body - and, more explicitly, with her Images of garments and accessories once owned by victims of the atomic blast in Hiroshima.0Essays featured in this volume reveal the past as the wellspring of lshiuchi's work and the present moment as her principal subject. 0Exhibition: J. Paul Getty Museum, Los Angeles, USA (06.10.2015-21.02.2016)